(untitled) (Journal of Information Technologies in Education (ITE), 2014)
This article investigates the possibility of using didactic webinars for implementing educational and scientific activities of highly qualified personnel. Substantiated scientific - theoretical foundations of the webinar and discussed its advantages over classical seminar.Discovered practical problems that need solving during implementation webinars and electronic conferences.